3D BaTiO3 Flower Based Polymer Composites Exhibiting Excellent Piezoelectric Energy Harvesting Properties. Issue 16 (29th May 2020) - Jian, Gang; Jiao, Yong; Meng, Qingzhen; Shao, Hui; Wang, Fengwei; Wei, Zhaoyu
Abstract: Piezoelectric nanogenerators (PENGs) with good flexibility and high outputs have promising applications in harvesting mechanical energy and powering electronics. In this study, a synthesis of hierarchical BaTiO3 flowers (BTFs) and their filling into the polydimethylsiloxane (PDMS) matrix to obtain composites with excellent energy harvesting properties is reported. The BTF‐based PENG possesses a voltage of 260 V, a current of 50 µ A, and a power of 1728 µ W under a compression of 50 N at 3.5 Hz, which output power is two orders higher than that of polymer composites filled with BT nanoparticles. Simulation indicates that the high local stress at petals of BTFs is the main reason for the enhanced performances. The PENG shows good durability under 5000 cycles and lights up 58 commercial light emitting diodes and a display. The PENG generates 30–100 V in harvesting human motions of hand slapping and foot stepping and ≈50 V in harvesting the sport kinetic energy of basketball bouncing. This research presents a BTF‐based PENG with significantly enhanced energy harvesting performances for applications in micro/nanoenergy systems. Abstract : Hierarchical BaTiO3 flowers are synthesized and hybrid filled with carbon nanotubes into the polydimethylsiloxane matrix to prepare composites with excellent piezoelectric energy harvesting properties. Piezoelectric nanogenerator (PENG) possesses a voltage of 260 V, a current of 50 µA, and a power of 1728 µW. This research presents a BTF‐based PENG with significantly enhanced energy harvesting performances for applications in self‐powered systems.